Doctrine of Love in Writings of 14th-Century Persian Mystic Mahmud Kashani - V. A. Drozdov (Научный диалог)
The article is devoted to the work of Mahmud Kashani (d. 735/1334-35), who was a sheikh of the Suhravardiya Sufi order and the author of several significant works. The object of analysis was one of the parts of his most famous work — the prose treatise “The lamp that indicates the true path, and the key to a sufficient amount [of mystical knowledge]”. The article deals with the religious views and scientific heritage of Mahmud Kashani. A commented translation of part of the first section “On Love” from the tenth chapter “Explanation of mystical states” of the specified work is proposed. Since Mahmud Kashani is also credited with the poem “Treasures of Secrets and Symbols of the Righteous”, dedicated to the psychological aspects of mystical love, we have also translated one of its chapters. Comparison of fragments of these works shows significant discrepancies in the explanation of love, which may be due to the fact that the author expounds the concept of love of ascetic Sufism in the first essay, and Sufism “based on love” in the second. The second direction goes back to the composition of the “Revelation of Love” by the Persian mystical philosopher Ahmad Ghazali. It is also possible that ‘Izz ad-Din Mahmud is not the author of the poem “Treasures of Secrets…”.